하악골 재건을 위한 가상수술계획 시스템 - 김한나; 김영준; 조현철; 심응준; 이득희; 김래현; 박세형; 이정우 (한국CDE학회, 2016)
In this paper, we propose a virtual surgical planning system specialized to mandible reconstruction surgery. Mandible reconstruction surgery is one of the most difficult surgeries, even for experienced surgeons. Compared to the traditional surgical procedures, virtual surgical planning can reduce the operation time in operating room while expecting better surgical outcome with optimized planning. However, with existing software systems, it requires much time and manual operations in virtual surgical planning. To reduce preparation time and improve accuracy of virtual surgical planning, we have developed optimized functions for virtual surgical simulation of mandible reconstruction with user-friendly interface. We found that the proposed system shortened the preparation time by half compared to the existing system from the experiments. The proposed system supports surgeons to make accurate plan faster and easier. The virtually planned results are used to make surgical cutting guide by 3D printing, and this will enhance surgical performance in operating room.